Liar & spy - Stead, Rebecca (New York : Wendy Lamb Books, 2012)
Seventh-grader Georges adjusts to moving from a house to an apartment, his father's efforts to start a new business, his mother's extra shifts as a nurse, being picked on at school, and Safer, a boy who wants his help spying on another resident of their building.
Bulletin of the Center for Children's Books starre
Horn Book Starred
School Library Journal starred
Booklist, June 2012
Bulletin of the Center for Children's Books starre, September 2012
Horn Book Starred, September 2012
Keywords: Apartment houses -- Juvenile fiction; Families -- New York (State) -- New York -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Apartment houses -- Fiction; Family life -- New York (State) -- New York -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Spies -- Fiction; Apartment houses -- Fiction; Family life -- New York (N.Y.) -- Fiction; JUVENILE FICTION / Social Issues / General (see also headings under Family); Middle schools -- Fiction; School stories; Spy stories; Brooklyn (New York, N.Y.) -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Fiction; Brooklyn (New York, N.Y.) -- Fiction; Spy stories